Regulation of Murine Natural Killer Cell Development - Goh, Wilford; Huntington, Nicholas D. (Frontiers in Immunology, 2017)
Natural killer (NK) cells are effector lymphocytes of the innate immune system that are known for their ability to kill transformed and virus-infected cells. NK cells originate from hematopoietic stem cells in the bone marrow, and studies on mouse models have revealed that NK cell development is a complex, yet tightly regulated process, which is dependent on both intrinsic and extrinsic factors. The development of NK cells can be broadly categorized into two phases: lineage commitment and maturation. Efforts to better define the developmental framework of NK cells have led to the identification of several murine NK progenitor populations and mature NK cell subsets, each defined by a varied set of cell surface markers. Nevertheless, the relationship between some of these NK cell subsets remains to be determined. The classical approach to studying both NK cell development and function is to identify the transcription factors involved and elucidate the mechanistic action of each transcription factor. In this regard, recent studies have provided further insight into the mechanisms by which transcription factors, such as ID2, FOXO1, Kruppel-like factor 2, and GATA-binding protein 3 regulate various aspects of NK cell biology. It is also becoming evident that the biology of NK cells is not only transcriptionally regulated but also determined by epigenetic alterations and posttranscriptional regulation of gene expression by microRNAs. This review summarizes recent progress made in NK development, focusing primarily on transcriptional regulators and their mechanistic actions.